Railways in Sub-Saharan Africa - World Bank (World Bank, 2012)
The changed role of rail in Africa over the last thirty years has seen it move from a situation where many of the systems were carrying a high share of their country's traffic to one in which their market share has declined, their assets have steadily deteriorated, their quality of service has reduced, and they are in many instances only a minor contributor to solving the transport problems of the continent. The first railways south of the Sahara were built in South Africa in the 1860's and 1870's, with lines heading inland from the ports at Cape Town and Durban. The networks in what were then Cape Province, Natal and Transvaal continued to develop but it was not until the turn of the twentieth century that large-scale railway development began in other parts of the continent. In almost every case, the pattern was the same, with isolated lines heading inland from a port to reach a trading centre or a mine, and a few branch lines then being built over a period of time. As almost all the lines were constructed under colonial administrations, many of the lines were state-owned but several were also constructed as concessions or, in the case of some mineral developments, by the mining company as an integral part of its mining operation. Nevertheless, the rhetoric accompanying some of the transactions suggests that many politicians believe, or want to believe, that the concession award will be the prelude to very substantial investments by the concessionaires, particularly in infrastructure. To date, this has barely materialized, with most infrastructure improvements being done with international financial institution (IFI) or donor funds. The main issue for most sub-Saharan railways is whether concessioning is just a temporary solution or whether some alternative approach is needed to ensure a long-term future for railway systems providing acceptable levels of service.